Introduction to the Special Issue on the History of Counselling in Canada - Robertson, Sharon E.; Borgen, William A. (Canadian Journal of Counselling and Psychotherapy, 2016)
In this introduction to the CJCP special issue, History of Counselling in Canada, important foundations, milestones, trends, and issues in the history of counselling as a profession in Canada are highlighted. Special attention is given to the evolution of the Canadian Counselling and Psychotherapy Association (CCPA) from its beginnings in 1965 to the robust national professional organization it is today, based primarily on articles in COGNICA and The Canadian Journal of Counselling and Psychotherapy. The contributions to this special issue focus on particular aspects of the development of counselling in Canada: career counselling, the profession of guidance counsellors in Quebec, and CCPA accreditation of counsellor education programs.